How the PJ Masks become “PJ Heroes”: A contrastive corpus study of gender portrayal in dubbed children’s animation - De Ridder, Reglindis; Johansson, Annika (Journal of Audiovisual Translation, 2024)
In this study of dubbing for children, a quantitative and qualitative corpus analysis of a popular TV series were conducted. The corpus consists of 12 episodes of the animated series PJ Masks, and its corresponding Dutch (Pyjamahelden [Pyjamas heroes]) and Swedish (Pyjamashjältarna [Pyjamas heroes]) audiovisual translations. The focus of the analyses is the portrayal of the main characters. In the light of ongoing criticism of children’s animation, regarding gender stereotyping and a lack of diversity, this translation analysis studies potential changes in gender representation. First, the character portrayal in all language versions was systematically analysed based on the characters’ utterances which were categorised into four categories (team spirit, problem-solving, need of assistance, and attention to relations). Subsequently, a closer qualitative analysis revealed some interesting translation shifts, particularly, in the Dutch target text. These were contrasted against the Swedish translation to check if this results in subtle or less subtle changes in the depiction of the heroes vis-à-vis the source text. Needless to say, such translation shifts in audiovisual translation for children and their effect on the representation of children in this multimodal glocal product is highly relevant amidst ongoing criticism of gender and diversity issues in children’s television. Lay Summary Several episodes of a popular animated series, PJ Masks, were analysed to check if the portrayal of the main characters changes when it is dubbed into Dutch and Swedish. This analysis was done because some people are concerned that animated series portray boys and girls in stereotypical ways. Both translations were closely compared to the original English version and revealed some interesting differences. This type of study helps us understand how children's animation can display different gender portrayals when dubbed into other languages.